2009
DOI: 10.1007/s10311-009-0215-0
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and availability of potentially toxic metals in soil in central area of Belgrade, Serbia

Abstract: Belgrade, capital city of Serbia, has over 1,600,000 inhabitants and over 400,000 vehicles trafficking every day on its streets. The investigation of soil pollution was performed by sequential extraction analysis to investigate the availability of potentially toxic metals (Zn, Cd, Pb, Co, Ni, Cu, Cr and Mn) under different oxidation and pH conditions. All investigated metals were mainly extracted from soils with neutral or acidic extractants. Serious pollution was observed along roads and streets with high tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Chromium occurs naturally in various oxidation states, with trivalent chromite Cr(III) being the most stable form, and hexavalent chromate Cr(VI) being highly mobile in soil and extremely toxic to living organisms [ 45 , 55 ]. Since Cr(III) is poorly soluble in water and completely precipitated at pH values above 5.5 [ 56 , 57 ], it can be assumed that in the investigated soils, which are characterised by neutral-to-alkaline pH, Cr(III) is present in a very stable form [ 47 ]. This was further confirmed by sequential analysis, where the proportion of Cr at all of the investigated sites was highest in the residual fraction (71.20–83.92%).…”
Section: Resultsmentioning
confidence: 99%
“…Chromium occurs naturally in various oxidation states, with trivalent chromite Cr(III) being the most stable form, and hexavalent chromate Cr(VI) being highly mobile in soil and extremely toxic to living organisms [ 45 , 55 ]. Since Cr(III) is poorly soluble in water and completely precipitated at pH values above 5.5 [ 56 , 57 ], it can be assumed that in the investigated soils, which are characterised by neutral-to-alkaline pH, Cr(III) is present in a very stable form [ 47 ]. This was further confirmed by sequential analysis, where the proportion of Cr at all of the investigated sites was highest in the residual fraction (71.20–83.92%).…”
Section: Resultsmentioning
confidence: 99%
“…Many studies showed that heavy metals in street dust do not degrade, but rather persist in street dust [13,14,15]. As street dust permeates the ecological environment by many means, such as surface runoff and atmospheric precipitation [16,17,18], heavy metals contained in street dust eventually enter the food chain, which are posing a potential risk to human health [19,20,21,22]. Many recent studies on heavy metals in street dust involved assessments of contamination levels [22,23,24], spatial distribution [11,22,24], and source identification [25,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Pollution of surface soils with heavy metals due to intensive industrialization and urbanization has become a serious concern in many developing countries (Ghariani et al 2010;Yaylalı-Abanuz 2011). Various anthropogenic activities associated with industrialization and urbanization, such as urban road traffic, diverse industrial manufacturing processes, waste material depositing and application of fertilizers, can lead to release of heavy metals into the environment.…”
Section: Introductionmentioning
confidence: 99%